OPTIMASI FERMENTASI ISOLAT ACTINOMYCETES SEBAGAI ANTIBAKTERI TERHADAP PERTUMBUHAN STAPHYLOCOCCUS AUREUS SECARA IN VITRO - Anastasia Joanne (2023)
Actinomycetes are Gram-positive bacilli and group of secondary metabolite-producing bacteria that are useful as antibacterials. The synthesis of secondary metabolites is influenced by nutrition, temperature, pH, and fermentation period. The optimal pH for the production of these metabolites is in the range of 6-8. Staphylococcus aureus is a human pathogens that cause multiple infections, which has a large incidence in the world. This study aims to determine the antibacterial activity of Actinomycetes isolates from Kebun Raya Bogor with fermentation optimization and pH control on the growth of S.aureus. The research used a true experimental design with Actinomycetes isolates obtained from soil in Kebun Raya Bogor on Starch Casein Agar (SCA) media and fermented in media consist of 1% glucose, 2% mannitol, 2% peptone which the pH was controlled within the range of 6.2 -6,8. Antibacterial test against S.aureus using well diffusion method with Nutrient Agar (NA) media. The inhibition zone diameters were analyzed using Kruskal Wallis Test and followed by Mann Whitney Test which had significant differences between groups. The average diameter of the inhibition zones produced at the fermentation period of the 3rd, 4th, and 5th days respectively were 3,73 mm; 6,05 mm; and 5,34 mm. Actinomycetes isolate has antibacterial potential against the growth of S. aureus with the largest average inhibition zone produced at the fermentation period of the 4th day which has moderate inhibition. The antibacterial activity of Actinomycetes isolates is achieved by inhibiting the synthesis of bacterial cell walls, nucleic acids, and proteins.